Chlorinated organic contaminants in fish from the South China Sea: Assessing risk to Indo-Pacific humpback dolphin. (August 2020) - Yu, Xiaoxuan; He, Qingya; Sanganyado, Edmond; Liang, Yan; Bi, Ran; Li, Ping; Liu, Wenhua
Abstract: Indo-Pacific humpback ( Sousa chinensis ) dolphins are primarily exposed to chlorinated organic contaminants through the consumption of contaminated fish. We assessed the potential risk of chlorinated organic contaminants to Indo-Pacific humpback dolphins by determining the concentration of 21 organochlorine pesticides (OCPs) and 28 polychlorinated biphenyls (PCBs) in 14 fish species collected from the South China Sea coastal waters. The results of the study showed that bioaccumulation of OCPs and PCBs was influenced by sampling location, fish species, and fish niche. The average ∑DDT (Dichlorodiphenyltrichloroethane) concentration was 3 times higher in benthopelagic fish (488 ng/g) compared to pelagic-neritic fish (155 ng/g) from Jiangmen, whereas an opposite pattern of the lower DDTs concentration in benthopelagic and demersal fish compared to pelagic fish from Zhuhai ( p  < 0.05). Furthermore, the molecular diagnostic ratios using DDT and its metabolites (DDT/(DDD + DDE) were less than one, suggesting the DDT contamination at Zhuhai and Jiangmen may due to the historical agricultural usage of the lands. The reference dose-based (RfD) risk quotient (RQ) suggested that DDTs are potential risk in Qinzhou, which is in accordance with the high DDTs concentration found in fishes captured in Qinzhou. The RfD risk quotient of PCBs is at potential risk for all sites (RQ > 100), except Xiamen and Qinzhou. A highest average ∑DDT concentration was observed Qinzhou. This study showed that fish consumption might pose a health risk to Indo-Pacific humpback dolphins. However, further studies are required to determine the contribution of fish niche to the overall risk. Graphical abstract: Image 1 Highlights: Concentrations of OCPs and PCBs in fish were influenced by fish niche and location. ∑PCBs were significantly higher in demersal than benthopelagic and pelagic fish. ∑OCPs were significantly higher in benthopelagic than demersal and pelagic fish. PCBs could be potential risk to Indo-Pacific humpback dolphins except at two sites. Abstract : This study showed that fish consumption might pose a health risk to Indo-Pacific humpback dolphins. Shoreline land use patterns and the fish habitat (pelagic, benthopelagic, pelagic or demersal) influenced the POPs levels in the fish.